Implementation of Accrual Based Accounting at PMI City of Surakarta - Sri Partini; Dian Noor Citra Perdana (Nur Science Institute, 2022)
Community organizations, non-profit organizations must be responsible for all operational activities of the organization. This includes financial accountability to the public. Accrual basis accounting method financial statements are more recommended than cash basis accounting. Purpose: to find out the implementation of accrual basis accounting at PMI Surakarta and its benefits. Method: This research is a qualitative descriptive study with data collection, data observation with in-depth interviews and documentation and field studies at PMI Surakarta City during the implementation of accrual basis accounting in January - June 2022. Results: There are changes in financial performance from the process of implementing cash basis accounting to accrual basis. Changes in the fundamental accounting process in the accounts of income, expenses, expenses. For example, depreciation costs, accumulated depreciation, consumable costs, logistics inventory stock, old-age insurance costs, holiday allowance costs have changed more with the application of this accrual basis by recording according to their historical value. This change is influenced by the process of recognizing revenues, expenses and expenditures, the process of recording assets and liabilities as well as measuring the historical value of financial transactions that occur. Conclusion: Assessment of organizational financial performance from the implementation of accrual basis accounting in financial reporting at PMI Surakarta City becomes more useful. Financial reports with accrual basis accounting are more accurate, more realistic, have more complete data presentation and can be used as a basis for developing management and organizational activities in the future.